C. elegans colony formation as a condensation phenomenon - Yuping Chen (Nature Portfolio, 2021)
Phase separation phenomena have emerged as being of critical importance in biology. Here, using colony formation in C. elegans as model, the authors demonstrate that the basic concepts that underpin phase separation at a molecular level also apply to collective phenomena at the level of a population of organisms.